Upbringing and education of children in context letters of Pythagorean woman philosophers - Vitalii Turenko (Філософія освіти, 2021)
The article reveals in detail the understanding of raising children in the context of two pseudo-epigraphic letters of Pythagorean wonan thinkers – Theano and Myia of Crotone. Based on these letters, it was found that pedagogical issues were important in general for the whole Pythagorean tradition. In fact, we can say that this early Greek philosophical school was the first to systematically and comprehensively approach the problem of upbringing and education in ancient society. It is hypothesized that this topic is not accidentally in the center of attention of these philosophers, because their authority was the greatest among all other representatives of this philosophical school. The author’s position is proved that Theano of Crotone letter to Eubule focuses on moderation in education, which is aimed at avoiding luxury, fulfilling all children’s whims, comfort. This is the purpose of hardening in difficult circumstances in order to withstand with dignity all the potential difficulties of adult life. Accordingly, if you do not raise a child in certain restrictions, then, according to Theano, it may well be unprepared for certain trials that may occur. The thesis is substantiated that the key task of upbringing and education, according to Myia of Crotone letter, is moderation, prudence and balance, which is based on both archaic elements and Hellenistic plots, which testifies to the skill of writing this letter. It is revealed that the Pythagorean principles of education, according to both philosophers, have no gender difference. This is because both girls and boys, if they grow up in luxury, comfort and do not know the limitations, can potentially become dangerous both for themselves and for society as a whole. It is emphasized that according to the style of writing, these letters are not so much moral and ethical as paraenetic epistolary genre, ie they act as advice on the upbringing and education of the younger generation. Because of this, these letters are such sources of ancient culture, which are one of the few that are devoted to the philosophical understanding of upbringing and education.